Development of Solar-powered Automatic Fertilizer System in Chili Fertigation Technology - Shamsuddin, Nur Arni Munirah; Abdullah, Mohd Noor (Evolution in Electrical and Electronic Engineering, 2020)
This paper elucidates the concept of a solar-powered automatic fertilizer system, where the farmers are able to control the injection of fertilizer intake with the intention of tackling the overdose fertilizer intake and electricity accessibility issues.  The main objectives of this paper are to design a photovoltaic (PV) system for automatic fertilizer system by considering the total of 300 chili crops, to develop an algorithm that can automatically agitate a proper proportion of fertilizer and to design a prototype for the development of the solar-powered automatic fertilizer system in chili fertigation technology. Arduino UNO is selected as the microcontroller to program the system while sensors such as EC sensor, ultrasonic sensor and flow rate sensor are used to initiate the agitation of fertilizer A, fertilizer B and water into the mixer tank. The system has been built accordingly and the performance of the system is tested. As a consequence, the result shows that the system is able to run with the aid of solar energy and the overall concept of the system can be implemented for the real application of the fertigation system.